"Now We Are Seeing the Tides Wash In": Trauma and the Opioid Epidemic in Rural Appalachian Ohio. (11th February 2021) - Schalkoff, Christine A.; Richard, Emma L.; Piscalko, Hannah M.; Sibley, Adams L.; Brook, Daniel L.; Lancaster, Kathryn E.; Miller, William C.; Go, Vivian F.
Abstract: Background : Ohio's opioid epidemic continues to progress, severely affecting its rural Appalachian counties—areas marked by high mortality rates, widespread economic challenges, and a history of extreme opioid overprescribing. Substance use may be particularly prevalent in the region due to interactions between community and interpersonal trauma. Purpose/Objectives : We conducted qualitative interviews to explore the local context of the epidemic and the contributing role of trauma. Methods : Two interviewers conducted in-depth interviews ( n = 34) with stakeholders in three rural Appalachian counties, including healthcare and substance use treatment professionals, law enforcement officials, and judicial officials. Semi-structured interview guides focused on the social, economic, and historical context of the opioid epidemic, perceived causes and effects of the epidemic, and ideas for addressing the challenge. Results : Stakeholders revealed three pervasive forms of trauma related to the epidemic in their communities: environmental/community trauma (including economic and historical distress), physical/sexual trauma, and emotional trauma. Traumas interact with one another and with substance use in a self-perpetuating cycle. Although stakeholders in all groups discussed trauma from all three categories, their interpretation and proposed solutions differed, leading to a fragmented epidemic response. Participants also discussed the potential of finding hope and community through efforts to address trauma and substance use. Conclusions: Findings lend support to the cyclical relationship between trauma and substance use, as well as the importance of environmental and community trauma as drivers of the opioid epidemic. Community-level and trauma-informed interventions are needed to increase stakeholder consensus around treatment and prevention strategies, as well as to strengthen community organization networks and support community resilience. Supplemental data for this article is available online at https://doi.org/10.1080/10826084.2021.1887248 .